2019
DOI: 10.4103/lungindia.lungindia_86_18
|View full text |Cite
|
Sign up to set email alerts
|

A pilot project: 99DOTS information communication technology-based approach for tuberculosis treatment in Rajkot district

Abstract: Background:99DOTS (Directly Observed Treatment, Short course) is a low-cost, mobile phone-based technology that enables real-time remote monitoring of daily intake of treatment, first introduced by the Revised National Tuberculosis Programme under the national programme in 2015 in high-burden antiretroviral therapy (ART) centers. This project was launched for the first time in 2016 in Rajkot district, Gujarat, India, and hence this was an effort to evaluate 99DOTS.Objectives:The objective of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 3 publications
0
17
0
Order By: Relevance
“…Levels of patient engagement with 99DOTS in our study are similar to findings from the broader 99DOTS rollout to > 20 000 patients in Mumbai [ 4 ]. Higher 99DOTS engagement has been reported elsewhere [ 8 ]; however, lack of an objective adherence measure and methodological differences make comparison with our study difficult. Prior studies suggest that suboptimal engagement with DATs is context dependent.…”
Section: Discussionmentioning
confidence: 54%
“…Levels of patient engagement with 99DOTS in our study are similar to findings from the broader 99DOTS rollout to > 20 000 patients in Mumbai [ 4 ]. Higher 99DOTS engagement has been reported elsewhere [ 8 ]; however, lack of an objective adherence measure and methodological differences make comparison with our study difficult. Prior studies suggest that suboptimal engagement with DATs is context dependent.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, electronic drug monitoring has been studied for TB treatment adherence. 99DOTS, an adherence program launched in India in 2016, has shown mixed results [10][11][12][13]. Medication Event Monitoring Systems has also been associated with mixed reliability and efficacy [14][15][16], and video-observed therapy and wirelessly observed therapy [17,18] may face implementation challenges in low-resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…6 However, treatment outcomes did not improve, and both trials and programmatic research have shown variable uptake of DAT. [7][8][9][10] The 'DOT to DAT' trial aims to evaluate the effectiveness, implementation and cost-effectiveness of a culturally and contextually adapted version of 99DOTS in Uganda. 99DOTS is a low-cost DAT wherein patients self-report medication adherence by calling toll-free phone numbers hidden underneath pills in blister packs.…”
Section: Introductionmentioning
confidence: 99%